Understanding wittgenstein's Tractatus - "Frascolla, Pasquale" (London, 2007)
Understanding Wittgenstein's Tractatus provides an accessible and yet novel discussion of all the major themes of the Tractatus. The book starts by setting out the history and structure of the Tractatus. It then investigates the main dimensions of the early Wittgenstein's thought, corresponding to the division between what language can say by means of its propositions and what language can only show.
Keywords: "Wittgenstein, Ludwig"